Predictors of patients’ loyalty toward doctors on web-based health communities: cross-sectional study - Wu, Tailai; Deng, Zhaohua; Chen, Zhuo; Zhang, Donglan; Wu, Xiang; Wang, Ruoxi (JMIR, 2019)
Background: Web-based health communities provide means for patients to not only seek care but also to promote their relationship with doctors. However, little is known about the predictors of patients’ loyalty toward doctors in Web-based health communities.